Individual work-motive values: determinants and consequences for the appraisal of specific health-related work characteristics - Knardahl, Stein; Christensen, Jan Olav (Frontiers in Psychology, 2024)
The objectives of the present study were to determine whether (I) work-motive values influence the appraisal of specific work characteristics of significance for health and function and (II) subject variables impact work-motive values. Two aspects of work-motive values were studied: values that assign importance to pursuing one’s personal goals and interests, internally based work-motive values (IntWMVs), and values that assign importance to external factors, externally based work-motive values (ExtWMVs). These aspects of motive values, age, gender, skill level, managerial role, and specific psychosocial work characteristics were analyzed in a cross-sectional sample of 12,994 employees in 101 private and public organizations. Two-year follow-up prospective data from 6,252 employees in 69 organizations elucidated whether associations were stable over time. The results showed that IntWMV influenced reports of levels of control of decisions, empowering leadership, innovative climate, quantitative demands, feedback from work, and self-leadership. ExtWMVs were most consistently associated with role clarity. Skill level and managerial role were associated with reporting higher levels of IntWMVs and lower ExtWMVs. In conclusion, the present data support the assumption that work-motive values influence the appraisal, reporting, and consequently measurements of work characteristics. Managers differ from subordinates in work-motive values and may face challenges in ascertaining and supporting subordinates’ needs.